Freedom of information in Scotland in practice - Dunion, Kevin (Dundee University Press, 2011)
The only in-depth guide to Scotland's access to information regime. Written by Kevin Dunion, the first Scottish Information Commissioner, this uniquely informed text provides detailed commentary on the provisions of the Freedom of Information (Scotland) Regulations 2004. Fully referenced to the Commissioner's own decisions and court judgements, it also considers in detail key issues of interpretation since the law came into effect. It is an essential handbook for anyone working with or using freedom of information law in Scotland. The Freedom of Information (Scotland) Act: fully annotated and with case studies illustrating the practical application of the legislation The Environmental Information (Scotland) Regulations: detailed interpretation of these often overlooked rights, highlighting in particular the important differences with the general FOI law In-depth consideration of key issues of interpretation, including those exemptions concerning personal information, official advice and formulation of policy, together with the application of the 'harm' and 'public interest' tests Explains how the Commissioner's investigations and practice assessments are conducted, giving a unique insight into the Commissioner's role in determining appeals and ensuring adherence to the Code of Practice Considers the state of freedom of information in Scotland by comparing it to provisions and developments in the rest of the UK and internationally